Six-week intermittent exercise training with and without blood flow restriction on physiological responses and endurance performance in young adult men / Zafyrah Mior ... [et al.]. - Mior, Zafyrah; Linoby, Adam; Shamsuddin, Amirul; Mohd Dan, Azwa Suraya; Kamalden, Tengku-Fadilah; Nugraha, Reshandi; Lisboa, Felipe Domingos (2024)
Exercise training with blood flow restriction (BFR) has gained attention for its potential to enhance muscular strength and hypertrophy, yet its combined effects with high-intensity intermittent exercise training (IET) remain underexplored. This study addresses this gap by evaluating the impact of a 6-week IET program, with and without BFR, on endurance performance and physiological responses in recreationally active young adult men. Twenty-eight participants were pair-matched (using estimated and randomly assigned to IET-BFR (mean ± SD: age 21 ± 2 years, body mass 59 ± 9 kg, height 1.7 ± 0.09 cm) and IET-only (mean ± SD: age 21 ± 2 years, body mass 60 ± 8 kg, height 1.69 ± 0.08 cm) groups. The IET-BFR group performed high-intensity intermittent exercises with inflatable cuffs (154 ± 6 mmHg) for 19.5 ± 0.5 minutes, while the IET-only group trained without cuffs. Both groups completed 12 training sessions, with assessments conducted using the Yo-Yo Intermittent Recovery Level 1 test (Yo-Yo IR1), blood lactate levels, heart rate (HR), and rate of perceived exertion (RPE). Results revealed a significant improvement in Yo-Yo IR1 performance (IET-BFR: 1,444 ± 319 m vs. IET-only 1,330 ± 362 m; p < 0.05) and significantly lower blood lactate levels during the exercise tests (IET-BFR: 7.37 ± 1.84 mmol.L-1 vs. IET-only 8.33 ± 2.20 mmol.L-1; p < 0.05). No significant differences were observed in HR or RPE between the groups. These results indicate that integrating BFR into IET protocols could boost exercise performance, potentially by increasing the efficiency of lactate clearance.